LA FALTA DE NORMATIVA ESPECÍFICA DE PROCEDIMIENTO, EN LOS JUICIOS DE INSOLVENCIA - Tene Angamarca, Rodrigo Jamil (2015)
My thesis is oriented to the study on "The lack of specific rules of procedure, insolvency judgments"; This issue has been considered to be investigated because currently there is variety of processes that occur in the Specialized Unit Judicial Civil and Commercial Canton Loja, as there is an orderly process for judges to dictate the fulfillment of the proceedings in the same way insolvency proceedings; so it is necessary that the Judicial Council count on competent judges for the conduct, and to ensure due process as determined by the Constitution and the Organic Law of the Judicial Branch. Currently the insolvency is too general that leaves space for civil judges make extensive interpretations and processed at its discretion insolvency judgments. The theoretical and field work of this thesis allowed me to get clear and precise criteria foundations, the same that helped me to verification of objectives and testing of the hypothesis allowing me to support the proposed changes. In conclusion therefore, the need to reform the procedure under clears rules on insolvency judgments established by the Code of Civil Procedure.